Recycled Steel Fiber-Reinforced Mortar with Embedded Structural Health Monitoring for Sustainable Construction - Amjad, Umar; R. Irshidat, Mohammad; R. Maurya, Muni; Albeitjali, Naeem; K. Razack, Riyamol; Y. Kailani, Hashem; K. Sadasivuni, Kishor (Civil Engineering Journal, 2025)
The study examines the mechanical and microstructural performance of eco-friendly mortar mixes that incorporate Recycled Steel Fibers (RSF) derived from waste tires. Four mortar formulations with varying RSF content (0%, 0.5%, 1%, and 1.5% by volume) were evaluated for compressive strength, flexural strength, and electrical conductivity. Experimental results revealed that a 1.5% RSF mixture exhibited remarkable improvements in flexural strength, achieving a 67% increase compared to the control formulation while delivering a 12.6% enhancement in compressive strength. However, the 0.5% RSF mix showed reduced performance due to poor fiber dispersion, underscoring the importance of proper fiber distribution. Specific resistance decreased with RSF addition, indicating enhanced electrical conductivity, with the lowest specific resistance observed at 0.5% RSF on day 28. An empirical model using a fiber reinforcing index (ξ) was developed to predict strength behavior. A quadratic relationship was found to best describe compressive strength gains, while a linear model effectively captured the flexural strength trend. The models were calibrated using both experimental data and literature values, achieving high predictive accuracy. Electrical conductivity increased with RSF addition, and the slope of the specific resistance during loading correlated strongly with mechanical strength, highlighting its potential as a non-destructive structural health monitoring (SHM) indicator. SEM analysis confirmed improved matrix integrity and fiber–matrix interaction at the optimal 1% RSF content, which balanced strength gains and sensing capability. The study establishes RSF as a viable sustainable alternative to virgin steel fibers, providing both mechanical enhancements and self-sensing properties. This novel integration of electrical monitoring with mechanical testing and modeling provides new insights into recycled-fiber composites by enabling simultaneous enhancement of structural performance and real-time damage monitoring.